1997
DOI: 10.1111/j.1365-2672.1997.tb02867.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Burkholderia pseudomallei from soil using selective culture techniques and the polymerase chain reaction

Abstract: An environmental soil survey to detect Burkholderia pseudomallei was performed during the dry and wet seasons in Darwin, Northern Territory, Australia. Soil was sampled at regular intervals during a 15-month period at different depths from areas which were representative of the local, soil environment. Selective culture techniques using Ashdown's and Galimand and Dodin's methods and the polymerase chain reaction (PCR) using specific 16S rRNA primers were used to detect and identify the organism and determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 19 publications
3
74
0
Order By: Relevance
“…B. pseudomallei is endemic to Southeast Asia (Leelarasamee, 1998;Perret et al, 1998) and Northern Australia (Brook et al, 1997) where it was first recognised during the early 20th century. Since the 1960s B. pseudomallei has come to prominence in other parts of the world through infection of Vietnam veterans and, more recently, as a potential biological weapon (Josephson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…B. pseudomallei is endemic to Southeast Asia (Leelarasamee, 1998;Perret et al, 1998) and Northern Australia (Brook et al, 1997) where it was first recognised during the early 20th century. Since the 1960s B. pseudomallei has come to prominence in other parts of the world through infection of Vietnam veterans and, more recently, as a potential biological weapon (Josephson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Additional molecules were captured for organisms that also had representation in the captured extraction and library blanks, though the levels identified in the SK8 library are lower than those in the negative controls. Aside from M. leprae, the only other organism unique to this sample was Burkholderia pseudomallei, a pathogenic organism responsible for melioidosis in humans; however, this organism can also survive in soil and water [23], and without a proper control sample for comparison, an environmental origin cannot be excluded.…”
Section: Analysis Of the Mycobacterium Leprae Positive Control Librarymentioning
confidence: 99%
“…When specific assays are conducted in an effort to diagnose glanders, serology may be complicated by cross-reactivity between B. mallei and B. pseudomallei antisera. Although PCR assays for B. mallei have been available since the late 1990s, a search of the medical literature reveals no documentation of their use in a comparative study (Brook et al, 1997;Merritt et al, 2006). In the study reported here, PCR, culture and histopathology were compared for diagnostic applicability.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in disease prevalence elsewhere in the world is often attributed to the reduced reliance on equids for transportation and work. B. mallei is closely related to Burkholderia pseudomallei, the cause of melioidosis; however, B. pseudomallei is a motile bacillus with the ability to survive more effectively in the environment (Brook et al, 1997;Carr & Waag, 2007;Khan et al, 2012;Larsen & Johnson, 2009). …”
Section: Introductionmentioning
confidence: 99%